2011
DOI: 10.4067/s0716-97602011000300010
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous periodicity of drosophila mtDNA: new refutations of neutral and nearly neutral evolution

Abstract: We found a consistent 3-site periodicity of the χ 2 9 values for the heterogeneity of the distribution of the second base in relation to the fi rst base of dinucleotides separated by 0 (contiguous), 1, 2, 3 … 17 (K) nucleotide sites in Drosophila mtDNA. Triplets of χ 2 9 values were found where the fi rst was over 300 and the second and third ranged between 37 and 114 (previous studies). In this study, the periodicity was signifi cant until separation of 2011K, and a structure of deviations from randomness amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…High non-random internucleotide interactions are then expected as they were found in Bernardi's isochors (Bernardi, 1993(Bernardi, , 2007) and Karlin's signatures (Karlin and Mrazek, 1997). We found strong interactions among the nucleotides of a dinucleotide when they were separated by 0 (consecutive), 1, 2 … K nucleotide sites (Valenzuela, 2009(Valenzuela, , 2010(Valenzuela, , 2011(Valenzuela, , 2012Valenzuela et al, 2010). Also we found a periodicity every 3 sites not related to protein coding functions, in prokaryote DNA and mtDNA but not in eukaryote DNA (we recently found periodicities in eukaryotes, Solar et al, 2012).…”
Section: Interactions and Periodicities Of Nucleotidesmentioning
confidence: 65%
See 2 more Smart Citations
“…High non-random internucleotide interactions are then expected as they were found in Bernardi's isochors (Bernardi, 1993(Bernardi, , 2007) and Karlin's signatures (Karlin and Mrazek, 1997). We found strong interactions among the nucleotides of a dinucleotide when they were separated by 0 (consecutive), 1, 2 … K nucleotide sites (Valenzuela, 2009(Valenzuela, , 2010(Valenzuela, , 2011(Valenzuela, , 2012Valenzuela et al, 2010). Also we found a periodicity every 3 sites not related to protein coding functions, in prokaryote DNA and mtDNA but not in eukaryote DNA (we recently found periodicities in eukaryotes, Solar et al, 2012).…”
Section: Interactions and Periodicities Of Nucleotidesmentioning
confidence: 65%
“…Mutation and genetic drift could transitorily construct some DNA segments with hermeneutical (meaning sense, Valenzuela, 2009Valenzuela, , 2011 value, but, they cannot maintain them. Drift cannot drive evolution.…”
Section: The Origin Of the Most Important Errors In Nte And N-ntementioning
confidence: 99%
See 1 more Smart Citation
“…Is this deviation restricted to 17 sites of separations? Our study showed that significant values were found up to 2000 and more sites of separation [10, 13]; thus these interactions cannot be produced by coding or non-coding functions or any structural restrictions (this DNA has less than 20,000 bp, most of it is coding DNA and both strands are coding strands. Large separations imply that the first base is in one coding segment and the second is in another coding segment).…”
Section: Main Textmentioning
confidence: 88%
“…Table 2 shows the analysis for the mtDNA of Drosophila melanogaster (taken and adapted from [8] and [10], see the figure of base distribution in [10]). We observe the enormous deviation from neutrality of the total set of dinucleotides from 0 to 17 sites of separation.…”
Section: Main Textmentioning
confidence: 99%